2010
DOI: 10.1001/archinternmed.2010.26
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of (R,S)-Methadone by (R)-Methadone

Abstract: Substitution of (R,S)-methadone by (R)-methadone reduces the QTc interval value. A safer cardiac profile of (R)-methadone is in agreement with previous in vitro and pharmacogenetic studies. If the present results are confirmed by larger studies, (R)-methadone should be prescribed instead of (R,S)-methadone to reduce the risk of cardiac toxic effects and sudden death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 29 publications
5
50
0
1
Order By: Relevance
“…hERG channel studies have shown that S-methadone is about three times more potent than the therapeutic R-enantiomer in inhibiting the repolarizing current [25,26]. Substitution of racemic methadone by R-methadone has been shown to reduce the QT interval prolongation observed with racemic methadone [27]. There are no non-clinical data on the two enantiomers of terodiline but QTc interval prolongation by racemic terodiline has been shown clinically to be exclusively due to its S-enantiomer [28].…”
Section: Overall Comments On Ich E14 Qanda Documentsmentioning
confidence: 99%
“…hERG channel studies have shown that S-methadone is about three times more potent than the therapeutic R-enantiomer in inhibiting the repolarizing current [25,26]. Substitution of racemic methadone by R-methadone has been shown to reduce the QT interval prolongation observed with racemic methadone [27]. There are no non-clinical data on the two enantiomers of terodiline but QTc interval prolongation by racemic terodiline has been shown clinically to be exclusively due to its S-enantiomer [28].…”
Section: Overall Comments On Ich E14 Qanda Documentsmentioning
confidence: 99%
“…On the other hand, elevated (S)-methadone causes cardiotoxicity by prolonging the QT interval and subsequently leads to torsade de pointes by blocking the voltage-gated potassium channel of the human ether-ago-go related gene (hERG) (14,15). This stereo-selective cardiotoxicity is attributed to (S)-methadone being 3.5 times more potent than (R)-methadone in blocking the hERG channel (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Blood samples for determination of R-and S-methadone plasma concentrations were taken immediately before intake of methadone on days Ϫ4, Ϫ3, Ϫ2, 2, 3, 4, 5, and 6 and on day Ϫ1 (methadone alone [reference]) and day 7 (methadone coadministered with telaprevir [test]). Blood samples were collected immediately predose and at 0.5, 1, 1.5, 2, 2.5, 3,4,5,6,8,12,16, and 24 h postdose.…”
Section: Methodsmentioning
confidence: 99%
“…Methadone is a synthetic narcotic analgesic that is administered as a combination of R-and S-isomers, with the R-isomer being mainly responsible for the opioid effect (6,7), whereas the S-isomer has been linked to prolongation of the corrected QT (QTc) (where QT represents the time between the start of the Q wave and the end of the T wave) (8). Methadone is primarily metabolized by N-demethylation to an inactive metabolite, 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidene (EDDP).…”
mentioning
confidence: 99%